Roaring transgression: Lisbon’s downtown nightclubs in the 1920s - Vaz, C. (International Conference on Night Studies, 2024)
In 1920s Lisbon, a specific kind of space branded the city’s image and nightlife: the new restaurant-dancing clubs located in the central areas of Baixa-Chiado and Restauradores. These clubs were often represented in the press, literature, and arts as symbols and evidence of a modern and cosmopolitan way of life in the Portuguese capital. Simultaneously, these spaces were also associated with several transgressions, both legal (such as gambling, prostitution, or the use of drugs) and moral (such as excessive nightlife, sexual promiscuity and deviation, or heavy drinking)—behaviours condemned by society and regarded as threats to public morality and decency. This presentation will focus on the presence in these clubs of women and men who defied the gender conventions of the time, both through the image they adopted and the behaviours or sexual preferences they exhibited, to analyse the role that they play in the characterization of these spaces. Based on published sources, such as the press, literature, and memoirs, and iconographic sources, this historical approach will analyse and contextualise spaces and practices of sociability and lifestyles that shaped the identities of individuals, groups, and places.